Math teaching resources in Latin American primary classrooms: Availability and impact on student learning - Murillo Torrecilla, Francisco Javier; Román Carrasco, Marcela; Atrio Cerezo, Santiago (Education Policy Analysis Archives, 2016)
This article describes the availability of different mathematics teaching resources in primary classrooms in Latin America to determine whether it affects student performance. A study was developed exploiting the data collected by SERCE (UNESCO) assessment, using 4-level multilevel models. The sample includes more than 8,000 classrooms in 3rd and 6th grade within 3,000 schools and 16 Latin-American countries, with a total amount of 180,000 students. On one hand, the results show there are significant gaps and differences in availability to specific learning resources for Latin American students in elementary classrooms. The analysis provides evidence that within classes where different resources are handy, students achieve higher performance.